ELECTRORESPONSIE BEHAVIOR OF POLYELECTROLYTE GELS (ACRYLIC ACID-CO-N-N' METHYLENE BISACRYLAMIDE) UNDER THE INFLUENCE OF ELECTRIC FIELD - Nguyen Phuong Hoai Nam; Eduado Mendes (ASEAN Journal on Science and Technology for Development, 2007)
Polymer gels which were synthesized from acrylic acid and N-N’ methylene bisacrylamide exhibited electrical sensitive behavior. Their swelling properties and electroresponsive behavior were studied. The results indicated that the water take-up ability of the hydrogel increased with the decreased N-N’ methylene bisacrylamide content within the network. The hydrogel membranes swollen in a neutral NaCl solution, bent toward the cathode under non-contact DC electric fields, and their bending speed and equilibrium strain increased with the increased of applied voltage. In addition, the effect of crosslinker concentration of N-N’ methylene bisacrylamide on bending behavior of the gels have been studied. The equilibrium strain decreased as the crosslinker concentration increased. By changing the direction of the applied potential cyclically, the hydrogel membranes exhibited good reversible bending behavior. The bending of the hydro gel membranes was initially explained by a bending theory of polyelectrolyte hydrogel based on the charge of osmotic pressure due to the ion concentration different between the inside and the outside of the network.